The hedging ability of gold, silver, and bitcoin against inflation in ASEAN countries - Loke, Mei Ying (2021)
The aim of this paper is to examine the hedging ability of gold, silver, and Bitcoin against inflation in ASEAN countries. This paper uses monthly data covering the period from July 2001 to May 2020 for regression tests of gold and silver. In contrast, the regression test for Bitcoin is conducted after May 2012. First, this paper explains the average asset returns using an EGARCH model, followed by a quantile regression model to examine whether the hedging ability of gold, silver, and Bitcoin against inflation remains equally strong in several bearish and bullish conditions. The result shows that gold and Bitcoin serve as a hedge during average and bullish conditions but not bearish conditions. There is evidence that silver acts as a hedge only in bullish conditions. Besides, this paper also finds that the haven property of gold, silver, and Bitcoin against inflation is realized solely during the bearish trend.